The impact of fiscal policy on economic activity over the business cycle - evidence from a threshold VAR analysis - Anja Baum; Gerrit B. Koester (Deutsche Bundesbank, 2011)
Does the state of the business cycle matter for the effects of fiscal policy shocks on GDP? This study analyses quarterly German data from 1976 to 2009 in a threshold SVAR, expanding the SVAR approach by Blanchard and Perotti (2002). In a linear benchmark SVAR, the analysis finds that hiking spending yields a short-term fiscal multiplier of around 0.70, while the fiscal multiplier resulting from an increase in taxes and social security contributions is -0.66. In addition, the threshold model derives fundamentally new insights on the effects of shocks, depending on when in the business cycle they occur, their size and their direction. Most importantly, fiscal spending multipliers are much larger in times of a negative output gap but have only a very limited effect in times of a positive output gap. Discretionary revenue policies, on the other hand, have a generally more limited impact. Our findings have important implications for the optimal fiscal policy mix over different stages of the business cycle. Various robustness checks, including a different threshold specification, do not influence these implications substantially.
Keywords: E62; E32; C54; 330; fiscal policy; business cycle; nonlinear analysis; fiscal multipliers